EKSISTENSI PRINSIP-RINSIP PENGEMBANGAN KURIKULUM PAI - Dolong, Jufri (Inspiratif Pendidikan, 2017)
Abstract: The existence of curriculum development in educational and teaching process found some basic things that must be considered by curriculum developers. First, it is the life philosophy of the nation, the school and the teacher itself. In this case the state of Indonesia is a state of Pancasila. So any school activities or teaching-learning process held in schools should be directed at the personal formation of learners toward the Pancasila people. Secondly, it is the expectation, demand and demand of the community for the education product. This means that the relevance of curriculum development should be maintained. In addition, local community conditions need to be considered in the development of the curriculum. Third, the important thing in curriculum development is the suitability of the curriculum with the condition of the learners. Because the curriculum is basically for learners. There fore in the curriculum development of curriculum developers should consider the characteristics of learners, both general and special characteristics. Fourth, the advancement of science and technology is something that can not be denied to be considered in the curriculum development process. In essence the curriculum contains science and technology (though not all curriculum content). But essentially existing science is developing and developing needs to be considered in the development of the curriculum.